Routes of non-traditional entry into buprenorphine treatment programs - Tiffany Champagne-Langabeer; Michael W. Swank; James R. Langabeer (BMC, 2020)
Abstract Background Excessive prescribing, increased potency of opioids, and increased availability of illicit heroin and synthetic analogs such as fentanyl has resulted in an increase of overdose fatalities. Medications for opioid use disorder (MOUD) significantly reduces the risk of overdose when compared with no treatment. Although the use of buprenorphine as an agonist treatment for opioid use disorder (OUD) is growing significantly, barriers remain which can prevent or delay treatment. In this study we examine non-traditional routes which could facilitate entry into buprenorphine treatment programs. Methods Relevant, original research publications addressing entry into buprenorphine treatment published during the years 1989-2019 were identified through PubMed, PsychInfo, PsychArticles, and Medline databases. We operationalized key terms based on three non-traditional paths: persons that entered treatment via the criminal justice system, following emergencies, and through community outreach. Results Of 462 screened articles, twenty studies met the inclusion criteria for full review. Most studies were from the last several years, and most (65%) were from the Northeastern region of the United States. Twelve (60%) were studies suggesting that the criminal justice system could be a potentially viable entry route, both pre-release or post-incarceration. The emergency department was also found to be a cost-effective and viable route for screening and identifying individuals with OUD and linking them to buprenorphine treatment. Fewer studies have documented community outreach initiatives involving buprenorphine. Most studies were small sample size (mean = < 200) and 40% were randomized trials. Conclusions Despite research suggesting that increasing the number of Drug Addiction Treatment Act (DATA) waived physicians who prescribe buprenorphine would help with the opioid treatment gap, little research has been conducted on routes to increase utilization of treatment. In this study, we found evidence that engaging individuals through criminal justice, emergency departments, and community outreach can serve as non-traditional treatment entry points for certain populations. Alternative routes could engage a greater number of people to initiate MOUD treatment.